Ovarian Reserve: A Critical Indicator of Female Reproductive Health - Ufnal, Julia; Wolff, Anna; Morawska, Maria; Lewandowska, Dominika; Rosińska-Lewandoska, Dominika; Szewczyk, Marcelina; Kożuchowska, Klaudia; Pilarz, Dawid; Jarosz, Kinga; Gruszka, Szymon (Journal of Education, Health and Sport, 2025)
Introduction: Ovarian reserve, defined as the quantity and quality of a woman’s remaining oocytes, is a critical determinant of fertility potential. The finite pool of oocytes established in utero declines progressively throughout life, which is a natural process but may result in diminished ovarian reserve (DOR) in some women. DOR can affect personal and demographic outcomes, as it is closely tied to reduced fertility potential. The global trend of delayed motherhood has further highlighted the need for accurate assessment tools and interventions to manage fertility challenges. This review aims to provide a concise overview of current knowledge on ovarian reserve, Moreover, it explores the factors affecting it to contextualize these insights within the broader challenges faced by women with diminished ovarian reserve. It also explores emerging potential interventions as well as innovative assessment tools that could enhance diagnostic accuracy. Materials and Methods: This narrative review was conducted using PubMed and Scholar database with following search terms: “ovarian reserve”, “diminished ovarian reserve”, “ovarian aging”, "ovarian insufficiency". Relevant publications were analyzed. Only articles in english were considered. State of Knowledge: Key markers for assessing ovarian reserve include anti-Müllerian hormone (AMH), antral follicle count (AFC), follicle-stimulating hormone (FSH), and inhibin B, each providing unique insights into ovarian function. AMH has emerged as a reliable marker due to its stability across the menstrual cycle, but the lack of standardization in assays limits its clinical utility. Factors such as obesity, thyroid dysfunction and endometriosis significantly impact ovarian reserve. Newly approaches, like machine learning models and AMH-based screening programs in countries like Portugal emerge. Additionally hormonal oral contraceptives affect the ovarian reserve marker values. DOR serves as an early marker for cardiovascular risk. Appropriate supplementation with folate and vitamin D may support ovarian reserve. Conclusions: Assessing ovarian reserve is crucial for predicting pregnancy outcomes, optimizing ART protocols, and guiding reproductive decisions. The diverse influence of discussed factors on ovarian function underscores the need for individualized evaluation. Emerging interventions, such as electro-acupuncture and autologous platelet-rich plasma injections, show promise for improving fertility outcomes. Further research and widespread screening programs are essential for advancing fertility management and understanding ovarian reserve globally.